(untitled) (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2017)
Photon \((γ)\) scalar \((φ)\) mixing in field theory involves fields those transform differently under Lorentz transformation. Usually, this takes place through loops involving bosonic fields of unified theories with that of electromagnetism. This type of interaction makes the medium dichoric, and the same induces optical activity, i.e., rotation of plane of polarization of electromagnetic field. In this paper, we study propagation of synchrotron photons in of a magnetized compact star magnetosphere, assuming \(φ\)\(γ\) interaction. Ways to look for polarimetric signatures of scalar photon coupling from the compact star electromagnetic signals is explored.